2016
DOI: 10.1111/ede.12189
|View full text |Cite
|
Sign up to set email alerts
|

Allocation of cytoplasm to macromeres in embryos of annelids and molluscs is positively correlated with egg size

Abstract: Evolutionary transitions between feeding and nonfeeding larval development have occurred many times in marine invertebrates, but the developmental changes underlying these frequent and ecologically important transitions are poorly known, especially in spiralians. We use phylogenetic comparative methods to test the hypothesis that evolutionary changes in egg size and larval nutritional mode are associated with parallel changes in allocation of cytoplasm to macromere cell lineages in diverse annelids and mollusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…In the majority of annelids and spiralians, the 1Q macromeres acquire a larger size and a larger allocation of cytoplasm and yolk, because the entire trunk ectoderm, mesoderm and endoderm will form from these lineages (Henry, 2014). However, in annelids with small eggs like Owenia , egg size has been correlated with the allocation of cytoplasm to the micromeres and with larval feeding mode (Jones et al, 2016). This reverse ratio between micromere and macromeres is present in another group of annelids, the sipunculans (Boyle and Rice, 2014; Gerould, 1906), where the larger micromere size is thought to contribute to the enlarged amount of apical/anterior ectoderm in the trochophore-like larva of this group, which has big prototrochal cells (Boyle and Rice, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of annelids and spiralians, the 1Q macromeres acquire a larger size and a larger allocation of cytoplasm and yolk, because the entire trunk ectoderm, mesoderm and endoderm will form from these lineages (Henry, 2014). However, in annelids with small eggs like Owenia , egg size has been correlated with the allocation of cytoplasm to the micromeres and with larval feeding mode (Jones et al, 2016). This reverse ratio between micromere and macromeres is present in another group of annelids, the sipunculans (Boyle and Rice, 2014; Gerould, 1906), where the larger micromere size is thought to contribute to the enlarged amount of apical/anterior ectoderm in the trochophore-like larva of this group, which has big prototrochal cells (Boyle and Rice, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Pernet and colleagues (Pernet and McHugh 2010;Pernet et al 2012;Jones et al 2016) have shown that cytoplasm is preferentially sequestered to macromeres during cleavage of annelid and gastropod embryos. A greater amount of cytoplasmic yolk in macromeres (which is typical of lecithotrophic larvae) is correlated with a slowdown in rate of development of midgut structures arising from these macromeres.…”
Section: Foregut Modules: Temporal Dissociation and Life History Tranmentioning
confidence: 99%